RECENT DEVELOPMENTS OF COMPUTATIONAL METHODS ON NATURAL CONVECTION IN CURVILINEAR SHAPED ENCLOSURES - Öztop, Hakan Fehmi; Selimefendigil, Fatih; Abu-Nada, Eiyad; Al-Salem, Khaled (Yildiz Technical Univ, 2016)
In this review work, thermal and flow fields due to natural convection of in curvilinear enclosures was conducted for different geometries using nnaofluids. Different computational techniques are applied to get results for this geometries. The main difficulties on this problem is to obtain of grid distribution. It was found that the geometry parameter is an important control parameter on heat and fluid flow in natural convection. In general, heat transfer increases with the addition of nanoparticle into the base fluid.
Keywords: Curvilinear geometry; natural convection; nanofluid